The God Mysticism Scale a Brief Version - Williamson, W. Paul; Chen, Zhuo; Hood, Ralph W. Jr. 1942- (2019)
This paper presents two studies concerned with developing a brief version of the 32-item God Mysticism Scale (GMS; Hood Jr. and Williamson Journal of Psychology and Christianity, 19(3), 232-244, 2000). Study 1 submitted 12 representative items from the GMS to an exploratory factor analysis and found a two-factor solution (Interpretation, 6 items; Experience, 6 items) that was used to constitute the God Mysticism Scale-Brief (GMS-B). Study 2 examined the construct validity of the GMS-B through a confirmatory factor analysis. The two-factor solution was confirmed, and fit indices revealed a good fit of the model to the data. Other analyses of the GMS-B found sufficient internal consistency (Study 1, Interpretation, ? = .94, Experience, ? = .86; Study 2, Interpretation, ? = .93, Experience, ? = .84) and preliminary evidence for criterion validity with religious and spirituality measures. The two studies together indicate that the GMS-B is well grounded in theory, psychometrically sound, and useful as an economic measure of mysticism in God language.
Keywords: God mysticism; Mysticism; Religious Orientation; Scale construction; Spirituality